Preparation method and application of zinc-cobalt diatomic carbon dioxide electroreduction catalyst
By preparing zinc-cobalt diatom catalysts, the problem of low catalyst activity in the aqueous solution system was solved, and the efficient electrochemical conversion of CO2 to methanol was achieved, which improved the selectivity of methanol and reduced costs, which was of great significance to large-scale promotion.
Patent Information
- Application Number
- CN202510045732.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-13
AI Technical Summary
In the aqueous solution system, the existing catalyst has low activity and it is difficult to achieve efficient electrochemical conversion from CO2 to methanol, resulting in low selectivity and high cost of methanol, and it is difficult to achieve large-scale promotion of carbon dioxide electroreduction technology.
Using the preparation method of zinc-cobalt diatom carbon dioxide electroreduction catalyst, a zinc cobalt molecule, zinc salt, nitrogen-containing raw materials and conductive carbon materials are dissolved in an organic solvent, and heated and calcined to obtain atomically dispersed zinc-cobalt diatom catalyst. This catalyst achieves efficient electrochemical conversion of CO2 to methanol in an aqueous solution system.
It has achieved efficient electrochemical conversion from CO2 to methanol, with the selectivity of methanol up to 42%, which is low-cost and environmentally friendly, which is of great significance to the large-scale promotion of carbon dioxide electroreduction technology.
Smart Images

Figure CN119455958B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide electro-reduction catalysts, and in particular to a preparation method and application of a zinc-cobalt diatomic carbon dioxide electro-reduction catalyst. Background Art
[0002] The process of converting carbon dioxide (CO2) into methanol through electrochemical reduction not only helps reduce the concentration of greenhouse gases in the atmosphere, but also converts CO2 into high-value-added chemicals or fuels, thus realizing the recycling of carbon resources. Methanol, as an important clean fuel and chemical raw material, is in great demand in the chemical industry. In addition, this technology can reduce human dependence on fossil fuels, which has important practical significance for alleviating the dual pressures of energy and environment.
[0003] Compared with the traditional thermal catalytic process, the electrochemical reduction of CO2 to methanol has the following advantages: (1) Environmental friendliness: The electrochemical reduction process can be carried out at lower temperature and pressure, reducing energy consumption and environmental pollution; (2) Utilization of renewable energy: The process can utilize electricity provided by renewable energy sources such as wind power and hydropower to achieve sustainable energy utilization; (3) Controllable reaction path: By adjusting the electrocatalyst and reaction conditions, the products of CO2 reduction can be precisely controlled; (4) Strong technical compatibility: Electrochemical reduction technology can be combined with traditional chemical processes to improve the flexibility and efficiency of existing industries.
[0004] Although electrochemical reduction of CO2 to methanol has many advantages, it also faces some challenges and difficulties. Electrochemical reduction of CO2 to methanol is a six-electron process with a long reaction path and is prone to byproducts, resulting in low selectivity for methanol. The chemical inertness of CO2 molecules makes it difficult to activate, the kinetic process is slow, and a high overpotential is required to drive the reaction. Currently, the cost of electrochemical reduction of CO2 to methanol is relatively high, and further cost reduction is needed to achieve commercial application.
[0005] Most of the currently available literature and patents use ionic liquids as electrolytes, but it is still difficult to achieve efficient electrochemical conversion of CO2 to methanol in aqueous solution systems. As electrolytes, ionic liquids have the disadvantages of high cost, potential toxicity, and complex recovery and reuse, making it difficult to achieve large-scale promotion of CO2 electroreduction technology. In aqueous solution systems, existing catalysts have low activity and it is difficult to achieve efficient conversion of CO2 to methanol. Therefore, how to develop electrocatalysts with high activity, high selectivity, and high stability in aqueous solution systems is the key to achieving large-scale application of efficient CO2 electroreduction technology. Summary of the invention
[0006] The present invention aims to overcome the problem of low catalytic activity of catalysts for electrochemical reduction of CO2 to methanol in an aqueous solution system in the prior art, and provides a preparation method and application of a zinc-cobalt diatomic carbon dioxide electroreduction catalyst. The prepared zinc-cobalt diatomic catalyst can achieve efficient electrochemical conversion of CO2 to methanol in an aqueous solution system, is low-cost, and environmentally friendly, and is of great significance to the large-scale promotion of carbon dioxide electroreduction technology.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst comprises the following steps:
[0009] (1) dissolving a macrocyclic cobalt molecule, a zinc salt, a nitrogen-containing raw material and a conductive carbon material in an organic solvent to obtain a mixture slurry, stirring and heating the mixture to volatilize the solvent to obtain a black solid; the molar ratio of the macrocyclic cobalt molecule to the zinc salt is 1:0.5-2; the molar ratio of the zinc salt to the nitrogen-containing raw material is 1:3-5; the mass molar ratio of the conductive carbon material to the macrocyclic cobalt molecule is 400 mg:0.05-0.2 mmol;
[0010] (2) Grinding the black solid obtained in step (1) and calcining it under the protection of an inert gas to obtain the zinc-cobalt diatomic carbon dioxide electroreduction catalyst.
[0011] In the preparation method provided by the present invention, by controlling the amount of macrocyclic cobalt molecules and zinc salts, an atomic-level dispersed zinc-cobalt diatomic catalyst can be obtained. By using a conductive carbon material as a substrate material, the conductivity of the catalyst can be enhanced and the CO2 electroreduction performance can be improved. Compared with the traditional metal salt impregnation method, zinc salts and nitrogen-containing raw materials are used as precursor raw materials in the present invention. After high-temperature calcination, the zinc atom site can obtain an unsaturated coordination structure rich in defects, enhance the activation performance of the zinc atom catalytic site to CO2, and improve the local intermediate concentration. In addition, using macrocyclic cobalt molecules as precursor raw materials, after high-temperature calcination, the cobalt atom can still maintain the coordination structure of Co-N4, enhance the activation performance of the cobalt atom catalytic site to the intermediate, thereby enhancing the final methanol conversion rate. This unique zinc-cobalt diatomic electronic structure can achieve efficient electrochemical conversion of CO2 to methanol. The catalyst prepared by the present invention has clear active sites, and proposes a step-by-step conversion strategy: the atomically dispersed metal zinc sites can convert carbon dioxide into a *CO intermediate, and the adsorption of the *CO intermediate is moderate; the metal cobalt sites uniformly dispersed around the zinc sites can further efficiently convert the *CO intermediate into methanol; the methanol selectivity can reach up to 42%, which is better than the performance of the existing disclosed catalyst using an aqueous solution system.
[0012] Preferably, the macrocyclic cobalt molecule in step (1) is a porphyrin cobalt or phthalocyanine cobalt molecule with a cobalt cation at the center of the macrocyclic molecule;
[0013] The zinc salt is one or more of acetylacetonate, acetate, citrate, nitrate, carbonate, chloride and hydrates thereof containing zinc cation;
[0014] The nitrogen-containing raw material is one or more of urea, dicyanamide and melamine;
[0015] The conductive carbon material is one or more of carbon nanotubes, graphene, acetylene black, Cabot black, and Ketjen black.
[0016] Preferably, in step (1), the mass volume ratio of the conductive carbon material to the organic solvent is 400 mg:50-150 mL.
[0017] Preferably, the organic solvent in step (1) is one of methanol, ethanol, isopropanol and acetone.
[0018] Preferably, the stirring time of the mixture slurry in step (1) is 1 to 6 hours.
[0019] Preferably, the grinding time of the black solid in step (2) is 10 to 30 minutes.
[0020] Preferably, the heating rate during calcination in step (2) is 5-10°C / min, the calcination temperature is 500-800°C, and the calcination time is 1-3h.
[0021] The present invention also provides an application of the zinc-cobalt diatomic carbon dioxide electro-reduction catalyst prepared by the above-mentioned preparation method in the electro-reduction of CO2 to methanol reaction.
[0022] Preferably, the method is: the zinc-cobalt diatomic carbon dioxide electroreduction catalyst is loaded on carbon paper to form a working electrode, and a three-electrode system is formed with a counter electrode and a reference electrode, and a CO2 electroreduction reaction is carried out in an H-type electrolytic cell.
[0023] Preferably, the loading amount of the zinc-cobalt diatomic carbon dioxide electroreduction catalyst on the carbon paper is 0.5-2 mg / cm 2 .
[0024] Therefore, the present invention has the following beneficial effects:
[0025] (1) The catalyst prepared by the present invention has clear active sites, and a step-by-step conversion strategy is proposed: the atomically dispersed metal zinc sites can convert carbon dioxide into a *CO intermediate, and the adsorption of the *CO intermediate is moderate; the metal cobalt sites uniformly dispersed around the zinc sites can further efficiently convert the *CO intermediate into methanol;
[0026] (2) The zinc-cobalt diatomic catalyst designed in the present invention can realize the efficient electrochemical conversion of CO2 to methanol in an aqueous solution system. It is low-cost and environmentally friendly, and is of great significance for the large-scale promotion of carbon dioxide electroreduction technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of the zinc-cobalt diatomic carbon dioxide electroreduction catalyst prepared in Example 1 of the present invention.
[0028] Figure 2 It is a transmission electron microscope image of the zinc-cobalt diatomic carbon dioxide electroreduction catalyst prepared in Example 1 of the present invention.
[0029] Figure 3 This is a spherical aberration-corrected electron microscope image of the zinc-cobalt diatomic carbon dioxide electroreduction catalyst prepared in Example 1 of the present invention.
[0030] Figure 4 It is a transmission electron microscope image of the zinc-cobalt metal nanoparticle carbon dioxide electroreduction catalyst prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0032] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0033] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with specific implementation methods, but it should be understood that these descriptions are only to further illustrate the features and advantages of the present invention rather than to limit the claims of the present invention.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Overall embodiment:
[0036] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst comprises the following steps:
[0037] (1) dissolving a macrocyclic cobalt molecule, a zinc salt, a nitrogen-containing raw material and a conductive carbon material in an organic solvent to obtain a mixture slurry, stirring and heating the mixture to volatilize the solvent to obtain a black solid; the molar ratio of the macrocyclic cobalt molecule to the zinc salt is 1:0.5-2; the molar ratio of the zinc salt to the nitrogen-containing raw material is 1:3-5; the mass molar ratio of the conductive carbon material to the macrocyclic cobalt molecule is 400 mg:0.05-0.2 mmol;
[0038] (2) Grinding the black solid obtained in step (1) and calcining it under the protection of an inert gas to obtain the zinc-cobalt diatomic carbon dioxide electroreduction catalyst.
[0039] As a specific implementation, the macrocyclic cobalt molecule in step (1) is a porphyrin cobalt or phthalocyanine cobalt molecule with a cobalt cation at the center of the macrocyclic molecule.
[0040] As a specific embodiment, the zinc salt in step (1) is one or more of acetylacetonate, acetate, citrate, nitrate, carbonate, chloride and hydrates thereof containing zinc cations.
[0041] As a specific implementation, the nitrogen-containing raw material in step (1) is one or more of urea, dicyanamide, and melamine.
[0042] As a specific implementation, the conductive carbon material in step (1) is one or more of carbon nanotubes, graphene, acetylene black, Cabot black, and Ketjen black.
[0043] As a specific implementation manner, in step (1), the mass volume ratio of the conductive carbon material to the organic solvent is 400 mg: 50-150 mL.
[0044] As a specific implementation, the organic solvent in step (1) is one of methanol, ethanol, isopropanol and acetone.
[0045] As a specific implementation manner, the stirring time of the mixture slurry in step (1) is 1 to 6 hours.
[0046] As a specific implementation manner, the grinding time of the black solid in step (2) is 10 to 30 minutes.
[0047] As a specific implementation manner, the heating rate during calcination in step (2) is 5-10°C / min, the calcination temperature is 500-800°C, and the calcination time is 1-3h.
[0048] Embodiment 1:
[0049] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, comprising the following steps:
[0050] (1) Dissolve 0.1 mmol of cobalt phthalocyanine, 0.1 mmol of zinc chloride, 0.4 mmol of dicyanamide, and 400 mg of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0051] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C at a heating rate of 10 °C / min in a tube furnace protected by argon gas and calcined at a constant temperature for 2 h to obtain a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, denoted as ZnCo-DAC-1; its scanning electron microscopy image is shown in FIG. Figure 1 As shown in the transmission electron microscopy images Figure 2 As shown in the figure, the spherical aberration corrected electron microscope image is as follows Figure 3 shown in; from Figure 1~Figure 3 It can be seen that the present invention can obtain atomic-level dispersed zinc-cobalt diatomic catalysts;
[0052] (3) ZnCo-DAC-1 was loaded on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0053] Embodiment 2:
[0054] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, comprising the following steps:
[0055] (1) Dissolve 0.1 mmol of cobalt phthalocyanine, 0.05 mmol of zinc chloride, 0.2 mmol of dicyanamide, and 400 mg of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0056] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, which was recorded as ZnCo-DAC-2;
[0057] (3) ZnCo-DAC-2 was loaded on carbon paper (loading amount 1 mg / cm 2), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0058] Embodiment 3:
[0059] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, comprising the following steps:
[0060] (1) Dissolve 0.1 mmol of cobalt phthalocyanine, 0.2 mmol of zinc chloride, 0.8 mmol of dicyanamide and 400 mg of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0061] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, which was recorded as ZnCo-DAC-3;
[0062] (3) ZnCo-DAC-3 was loaded on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0063] Embodiment 4:
[0064] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, comprising the following steps:
[0065] (1) Dissolve 0.05 mmol of cobalt phthalocyanine, 0.1 mmol of zinc chloride, 0.4 mmol of dicyanamide, and 400 mg of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0066] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, which was recorded as ZnCo-DAC-4;
[0067] (3) ZnCo-DAC-4 was loaded on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0068] Embodiment 5:
[0069] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, comprising the following steps:
[0070] (1) Dissolve 0.2 mmol of cobalt phthalocyanine, 0.1 mmol of zinc chloride, 0.4 mmol of dicyanamide, and 400 mg of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0071] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, which was recorded as ZnCo-DAC-5;
[0072] (3) ZnCo-DAC-5 was loaded on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0073] Comparative Example 1:
[0074] A method for preparing a zinc single-atom carbon dioxide electroreduction catalyst, comprising the following steps:
[0075] (1) Dissolve 0.1 mmol zinc chloride, 0.4 mmol dicyanamide and 400 mg Cabot carbon black in 100 mL ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0076] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a zinc single-atom carbon dioxide electroreduction catalyst, denoted as Zn-SAC;
[0077] (3) Zn-SAC was loaded on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0078] Comparative Example 2:
[0079] A method for preparing a cobalt single-atom carbon dioxide electroreduction catalyst, comprising the following steps:
[0080] (1) Dissolve 0.1 mmol of cobalt phthalocyanine and 400 mg of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0081] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a cobalt single-atom carbon dioxide electroreduction catalyst, denoted as Co-SAC;
[0082] (3) Co-SAC was loaded on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0083] Comparative Example 3 (the amount of macrocyclic cobalt molecules and zinc salts used exceeds the scope of the present invention):
[0084] A method for preparing a zinc-cobalt metal nanoparticle carbon dioxide electroreduction catalyst, comprising the following steps:
[0085] (1) Dissolve 0.3 mmol of cobalt phthalocyanine, 0.3 mmol of zinc chloride, 1.2 mmol of dicyanamide, and 400 mg of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0086] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C at a heating rate of 10 °C / min in a tube furnace protected by argon gas and calcined at a constant temperature for 2 h to obtain a zinc-cobalt metal nanoparticle carbon dioxide electroreduction catalyst, denoted as ZnCo-NP; its transmission electron microscopy image is shown in FIG. Figure 4 shown in; from Figure 4 It can be seen that when the amount of macrocyclic cobalt molecules and zinc salts exceeds the range of the present invention, zinc-cobalt metal nanoparticles will be generated, and atomically dispersed diatomic catalysts cannot be obtained;
[0087] (3) Load ZnCo-NP on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0088] Comparative Example 4 (without adding nitrogen-containing raw materials):
[0089] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, comprising the following steps:
[0090] (1) Dissolve 0.1 mmol of cobalt phthalocyanine, 0.1 mmol of zinc chloride, and 400 g of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0091] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, which was recorded as ZnCo-DAC-6;
[0092] (3) Load ZnCo-DAC-6 on carbon paper (loading amount 1 mg / cm 2), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0093] Comparative Example 5 (using ordinary cobalt salt instead of macrocyclic cobalt molecules):
[0094] A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, comprising the following steps:
[0095] (1) Dissolve 0.1 mmol of cobalt chloride, 0.1 mmol of zinc chloride, 0.4 mmol of dicyanamide and 400 g of Cabot carbon black in 100 mL of ethanol; stir the mixed slurry for 2 h, then heat to 70 °C and continue stirring until the solvent is completely evaporated to obtain a black solid;
[0096] (2) The obtained black solid was ground for 10 min and then transferred to a crucible; heated to 600 °C in a tube furnace protected by argon at a heating rate of 10 °C / min and calcined at a constant temperature for 2 h to obtain a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, which was recorded as ZnCo-DAC-7;
[0097] (3) ZnCo-DAC-7 was loaded on carbon paper (loading amount 1 mg / cm 2 ), to obtain a working electrode; using a porous platinum mesh as a counter electrode, a silver / silver chloride electrode as a reference electrode, and a 0.1 mol / L potassium bicarbonate solution as a cathode / anode electrolyte, the carbon dioxide electroreduction performance test was carried out in an H-type electrolytic cell, and the selectivity of the product was calculated. The test results are shown in Table 1; the reaction gas phase product was detected by gas chromatography, and the liquid phase product was detected by nuclear magnetic resonance hydrogen spectrum.
[0098] Table 1: Product selectivity test results
[0099]
[0100] As can be seen from Table 1, the zinc-cobalt diatomic carbon dioxide electroreduction catalysts prepared by the method of the present invention in Examples 1 to 5 have high catalytic activity in an aqueous solution system and can achieve efficient conversion of CO2 to methanol. The catalyst prepared by the present invention has clear active sites and proposes a step-by-step conversion strategy: atomically dispersed metal zinc sites can convert carbon dioxide into *CO intermediates and have moderate adsorption of *CO intermediates; metal cobalt sites uniformly dispersed around the zinc sites can further efficiently convert *CO intermediates into methanol.
[0101] However, the zinc single atom catalyst in Comparative Example 1 lacks a cobalt single atom catalytic site, resulting in the inability to further convert the *CO intermediate generated at the zinc single atom site, so no methanol can be detected in the product.
[0102] The cobalt single-atom catalyst in Comparative Example 2 lacks zinc single-atom catalytic sites, which results in the inability to provide a reaction environment rich in *CO intermediates. Therefore, the selectivity of methanol is significantly reduced compared with that in the example.
[0103] In Comparative Example 3, the amounts of macrocyclic cobalt molecules and zinc salts exceeded the scope of the present invention, resulting in the generation of cobalt-zinc metal nanoparticles, which were more susceptible to side reactions of water electrolysis, resulting in a significant increase in the proportion of hydrogen and a significant decrease in methanol selectivity.
[0104] In Comparative Example 4, no nitrogen-containing raw materials are added. Due to the lack of nitrogen, it is difficult for zinc atoms to form Zn-N4 structural sites, making it difficult to activate CO2 molecules and unable to efficiently generate *CO intermediates, resulting in a significant decrease in the selectivity of methanol compared with that in the example.
[0105] In Comparative Example 5, cobalt chloride is used instead of the macrocyclic cobalt molecule, resulting in the coordination structure of the cobalt single atom site no longer necessarily being the Co-N4 structure. The coordination environment of the cobalt single atom site is complex and diverse, and is no longer conducive to the production of methanol. Therefore, the selectivity of methanol is significantly reduced compared with that in the embodiment.
[0106] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a zinc-cobalt diatomic carbon dioxide electroreduction catalyst, characterized in that it comprises: Follow these steps: (1) dissolving a macrocyclic cobalt molecule, a zinc salt, a nitrogen-containing raw material and a conductive carbon material in an organic solvent to obtain a mixture slurry, stirring and then heating to volatilize the solvent to obtain a black solid; the molar ratio of the macrocyclic cobalt molecule to the zinc salt is 1:0.5-2; the molar ratio of the zinc salt to the nitrogen-containing raw material is 1:3-5; the mass molar ratio of the conductive carbon material to the macrocyclic cobalt molecule is 400 mg:0.05-0.2 mmol; the macrocyclic cobalt molecule is a porphyrin cobalt or phthalocyanine cobalt molecule with a cobalt cation at the center of the macrocyclic molecule; (2) Grinding the black solid obtained in step (1) and calcining it under the protection of an inert gas to obtain the zinc-cobalt diatomic carbon dioxide electroreduction catalyst.
2. The method for preparing the zinc-cobalt diatomic carbon dioxide electroreduction catalyst according to claim 1, characterized in that: The zinc salt in step (1) is one or more of acetylacetonate, acetate, citrate, nitrate, carbonate, chloride and hydrates thereof containing zinc cations; The nitrogen-containing raw material is one or more of urea, dicyanamide or melamine; The conductive carbon material is one or more of carbon nanotubes, graphene, acetylene black, Cabot black, and Ketjen black.
3. The method for preparing the zinc-cobalt diatomic carbon dioxide electroreduction catalyst according to claim 1, characterized in that: In step (1), the mass volume ratio of the conductive carbon material to the organic solvent is 400 mg:50-150 mL.
4. The method for preparing the zinc-cobalt diatomic carbon dioxide electroreduction catalyst according to claim 1 or 3, characterized in that: The organic solvent described in step (1) is one of methanol, ethanol, isopropanol and acetone.
5. The method for preparing the zinc-cobalt diatomic carbon dioxide electroreduction catalyst according to claim 1, characterized in that: The stirring time of the mixture slurry in step (1) is 1 to 6 hours.
6. The method for preparing the zinc-cobalt diatomic carbon dioxide electroreduction catalyst according to claim 1, characterized in that: The grinding time of the black solid in step (2) is 10 to 30 minutes.
7. The method for preparing the zinc-cobalt diatomic carbon dioxide electroreduction catalyst according to claim 1, characterized in that: The heating rate during calcination in step (2) is 5-10°C / min, the calcination temperature is 500-800°C, and the calcination time is 1-3h.
8. An application of a zinc-cobalt diatomic carbon dioxide electro-reduction catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Applied in the electroreduction of CO2 to methanol.
9. The use of the zinc-cobalt diatomic carbon dioxide electro-reduction catalyst according to claim 8, characterized in that the method is: the zinc-cobalt diatomic carbon dioxide electro-reduction catalyst is loaded on carbon paper to form a working electrode, and a three-electrode system is formed with a counter electrode and a reference electrode, and a CO2 electro-reduction reaction is carried out in an H-type electrolytic cell.
10. The use of the zinc-cobalt diatomic carbon dioxide electroreduction catalyst according to claim 9, characterized in that: The loading of zinc-cobalt diatomic carbon dioxide electroreduction catalyst on carbon paper is 0.5~2 mg / cm 2 .
Citation Information
Patent Citations
Catalyst for preparing synthesis gas by electrochemically reducing carbon dioxide and preparation method thereof
CN111871406A
Porous concave cubic CoNP@ CoSA-N-C catalyst, preparation method and application thereof
CN112886030A